The Formulation and Physical Evaluation Tests of Ethanol in Telang Flower (Clitoria ternatea L.) Extract Losio Form as Antioxidant - Jayanti, Merly; Ade Maria Ulfa; Angga Saputra Yasir (Biomedical Journal of Indonesia, 2021)
Background. Antioxidants are defined as compounds that are able to delay, slow down, or inhibit oxidation reactions. One of the plants that has the potential as natural antioxidants is the telang flower. The purpose of this study was to determine whether the ethanol extract of telang flower (Clitoria ternatea L.) can be formulated in a losion form that meets the requirements of the physical evaluation test and to determine the ethanol extract of telang flower (Clitoria ternatea L.) has antioxidant activity. Methods. The extraction using maceration techniques with 96% ethanol solvent. The yield obtained from the maceration technique was 29.16%. Phytochemical analysis of telang flowers contains alkaloids, flavonoids, polyphenols, saponins and tannins. Determination of the levels of flavonoids obtained levels of 10.05% and for polyphenols of 15.33%. Results. Telang flower extract (Clitoria ternatea L.) can be formulated into losions and meets the requirements of the physical evaluation test in the extract concentration of 0.1%. The losion of telang flower extract (Clitoria ternatea L.) with a concentration of 0.1% telang flower extract has very strong antioxidant activity because it has an IC50 value <50 ppm, and the IC50 yield of a losion with a concentration of 0.1% telang flower extract (Clitoria ternatea L.) of 37.92 ppm which means that it has very strong antioxidant activity. Conclusion. The formula of the telang flower extract lotion has strong antioxidant activity and protects the skin from free radicals.